2015
DOI: 10.4049/jimmunol.1501657
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Tumor Antigens in T Cell Immunotherapy

Abstract: Cancer immunotherapy is a rapidly evolving field that exploits T-cell responses to tumor-associated antigens to induce tumor rejection. Molecular identification of tumor rejection antigens has helped define several classes of antigens, including tissue-differentiation and tumor-germline antigens. The ability to genetically engineer antigen-specific receptors into T cells provides an opportunity to translate these findings into therapies. New immunotherapy agents, notably checkpoint inhibitors, have demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 50 publications
0
106
0
Order By: Relevance
“…One group of antigens are known as tumor associated antigens (TAA) which are antigens that are overexpressed in cancer cells but can also be found on normal tissues (19,20). These include CD19, PRAME, MAGE, ERBB2, p53, and L2A5 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Studies have shown that tumors possessing these antigens are more likely to induce tolerance and are less responsive to ICB (further explained below) (22,23).…”
Section: Tumor Immunosurveillance and Tumor Antigensmentioning
confidence: 99%
“…One group of antigens are known as tumor associated antigens (TAA) which are antigens that are overexpressed in cancer cells but can also be found on normal tissues (19,20). These include CD19, PRAME, MAGE, ERBB2, p53, and L2A5 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Studies have shown that tumors possessing these antigens are more likely to induce tolerance and are less responsive to ICB (further explained below) (22,23).…”
Section: Tumor Immunosurveillance and Tumor Antigensmentioning
confidence: 99%
“…Jager et al 1998; Knuth et al 1984; Lennerz et al 2005; Murray et al 1992; Pritchard et al 2015a; van der Bruggen et al 1991; Vella et al 2009), the translation of this to clinical application has largely resulted in low overall response rates (Ilyas and Yang 2015; Neller et al 2008), with some notable exceptions (e.g. Bollard et al 2014; Roskrow et al 1998; Tran et al 2014, 2016; Zacharakis et al 2018).…”
Section: Immunotherapeutic Potential Of Cancer Antigensmentioning
confidence: 99%
“…To sum up, the parameter x p can be interpreted as a measure of specificity of immunotherapeutic intervention. To present a microscopic view of the problem studied, we outline an interpretation in which x p integrates the basic mechanisms, such as the specific efficacy of the tumor-associated antigens, the ability of tumors to activate T-cell responses in-cluding the tumor recognition and the induction of cancer cell deaths [70]. By combining Eq.…”
Section: Diversification Of the Effects Of Immunotherapymentioning
confidence: 99%